Neodymium iron boron magnet and preparation method thereof

By diffusing the terbium in the neodymium iron boron body and performing specific heat treatment, a neodymium iron boron magnet with a coercive force conforming to a specific relationship was prepared, which solved the problem of unclear magnet coercive force relationship in the prior art, and improved production efficiency and magnet performance.

CN119786178APending Publication Date: 2025-04-08BAOTOU TIANHE MAGNETICS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411991226.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has failed to effectively explore the relationship between the coercive force and the initial coercive force after the grain boundary diffusion of sintered NdFeB magnet, which affects the performance and production efficiency of the magnet.

Method used

By diffusing terbium with a specific terbium weight gain content ΔW and a heat treatment process, a neodymium iron boron magnet with a coercive force in accordance with a specific relationship is prepared.

Benefits of technology

It has achieved accurate guidance on the production of neodymium iron boron magnets with target coercive forces, which improves production efficiency and accuracy, and meets the needs of high-performance magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223691850000121
    Figure BDA0005223691850000121
  • Figure BDA0005223691850000141
    Figure BDA0005223691850000141
  • Figure BDA0005223691850000151
    Figure BDA0005223691850000151
Patent Text Reader

Abstract

The invention discloses a neodymium iron boron magnet and a preparation method thereof. The neodymium iron boron magnet is obtained by diffusing terbium from a neodymium iron boron blank having a coercive force A0. The coercive force A1 of the neodymium iron boron magnet and the coercive force A0 of the neodymium iron boron blank satisfy the following relationship: A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)‑C; wherein a is a constant, a is ‑25.00 to ‑20.00, b is a constant, b is 32.00 to 40.00, C is a constant, C is 3.20 to 5.80; ΔW is the weight gain percentage of terbium; the units of A1 and A0 are both kOe; the thickness of the NdFeB blank is 2.5 mm to 8.0 mm. The NdFeB magnet of the present invention is obtained by diffusing terbium into the NdFeB blank, and the difference in coercivity between the two conforms to a certain relationship.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a neodymium iron boron magnet and a preparation method thereof. Background Art

[0002] Sintered NdFeB magnets are widely used due to their excellent magnetic properties such as high saturation induction, high coercivity and high magnetic energy product.

[0003] Generally, grain boundary diffusion of heavy rare earth elements is used to increase the coercivity of sintered NdFeB magnets, but there is no report that the coercivity of the NdFeB magnet obtained after diffusion conforms to a certain relationship with the coercivity of the NdFeB magnet before diffusion.

[0004] CN107799294A discloses a method for preparing NdFeB magnets by grain boundary diffusion, comprising selecting a suitable base NdFeB and cutting the base NdFeB magnet into thin slices with a thickness of less than 8 mm to obtain NdFeB thin slices, soaking the NdFeB thin slices in a hydrochloric acid solution or a nitric acid solution, and then drying; attaching a layer of heavy rare earth metal to the surface of the dried NdFeB thin slices by evaporation, vacuum infiltration, and then aging treatment to obtain the target NdFeB magnet. The patent document does not involve reports on whether the coercive force between the target NdFeB magnet and the base NdFeB conforms to a certain relationship.

[0005] CN105185498A discloses a rare earth permanent magnet material and a manufacturing method thereof, the manufacturing method comprising a multi-arc ion plating process and an infiltration process, wherein a metal containing a heavy rare earth element is deposited on the surface of a sintered NdFeB magnet by a multi-arc ion plating process, and the deposited sintered NdFeB magnet is heat treated. The sum of the intrinsic coercive force and the maximum magnetic energy product of the obtained rare earth permanent magnet material is greater than 66.8. The patent document does not involve the relationship between the coercive force of the obtained rare earth permanent magnet material and the coercive force of the initial sintered NdFeB magnet.

[0006] CN115662543A discloses an iterative prediction method for sintered NdFeB grain boundary diffusion products, including the steps of establishing a database, model evaluation, training and testing a regression model, training and testing a classification model, classification model prediction, regression model prediction, and iterative prediction. The patent document can first construct and learn a classification model to optimize the diffusion process of grain boundary diffusion, predict the relative importance of factors affecting grain boundary diffusion, and improve the prediction ability of the subsequent regression model for coercive force increment. The patent document does not consider the effect of the thickness of the magnet to be processed on diffusion, and is mainly used for the prediction of alloys of heavy rare earth elements, light rare earth elements, and non-rare earth elements as diffusion sources.

[0007] CN110120297A discloses a method for increasing the grain boundary diffusion depth of NdFeB, comprising the following steps: pretreatment; uniform coating; heat treatment process; the patent document firstly keeps the temperature at low temperature to allow the infiltrated material to enter the Nd-rich phase, then gradually increases the diffusion temperature to ensure that the infiltrated material diffuses to the center of the magnet as much as possible under the premise that a small amount of infiltrated material enters the main phase, and finally increases the diffusion temperature to allow the infiltrated material in the Nd-rich phase to enter the epitaxial layer of the NdFeB main phase grains. The patent document involves increasing the grain boundary diffusion depth of NdFeB. Summary of the invention

[0008] In view of this, one object of the present invention is to provide a neodymium iron boron magnet, which can be obtained by diffusing terbium into a neodymium iron boron blank, and the coercive forces of the two conform to a certain relationship. Another object of the present invention is to provide a method for preparing the neodymium iron boron magnet as described above, which can obtain a neodymium iron boron magnet with a specific coercive force. The preparation method can improve production efficiency and accuracy. The present invention adopts the following technical solution to achieve the above purpose.

[0009] On the one hand, the present invention provides a NdFeB magnet, which is obtained by diffusing terbium from a NdFeB blank having a coercive force A0, and the coercive force A1 of the NdFeB magnet satisfies the following relationship with the coercive force A0 of the NdFeB blank:

[0010] A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)-C;

[0011] Wherein, a is a constant, a is -25.00~-20.00, b is a constant, b is 32.00~40.00, C is a constant, C is 3.20~5.80; ΔW is the weight gain percentage of terbium; the units of A1 and A0 are both kOe;

[0012] The thickness of the NdFeB blank is 2.5 mm to 8.0 mm.

[0013] According to the NdFeB magnet of the present invention, preferably, the NdFeB blank is an R-Fe-B sintered magnet, with R2Fe 14 B is the main phase; among them, R is a rare earth element and must contain Nd.

[0014] According to the NdFeB magnet of the present invention, preferably, the NdFeB blank contains dysprosium; based on the total weight of the NdFeB blank, the dysprosium content is greater than 0 and less than or equal to 2.5wt%.

[0015] On the other hand, the present invention also provides a method for preparing a neodymium iron boron magnet, comprising the following steps:

[0016] (1) providing a neodymium iron boron blank having a coercive force A0, wherein the unit of A0 is kOe; and the thickness of the neodymium iron boron blank is 2.5 mm to 8.0 mm;

[0017] (2) According to the following formula, the weight gain percentage ΔW of terbium is determined, thereby determining the amount of terbium adhesion;

[0018] A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)-C;

[0019] Wherein, A1 is the coercive force of NdFeB magnet; the unit of A1 is kOe;

[0020] Among them, a is a constant, a is -25.00 to -20.00, b is a constant, b is 32.00 to 40.00, C is a constant, C is 3.20 to 5.80;

[0021] (3) Check 100×ΔW. If it is between 0.45 and 0.80, determine the amount of terbium deposition and execute step (4); otherwise, execute step (1) again.

[0022] (4) attaching the terbium-containing material to two oppositely disposed surfaces of the NdFeB blank according to the determined terbium attachment amount, thereby obtaining an attached magnet; wherein the two surfaces are perpendicular to the orientation direction of the NdFeB blank;

[0023] (5) The attached magnet is heat treated to obtain a NdFeB magnet.

[0024] According to the preparation method of the present invention, preferably, the NdFeB blank contains Pr and Nd; based on the total weight of the NdFeB blank, the PrNd content is 28.3-31.5wt%, and the weight ratio of Pr to Nd is 1:3-1:4.

[0025] According to the preparation method of the present invention, preferably, C is 3.60-5.50.

[0026] According to the preparation method of the present invention, preferably, the terbium-containing material is attached to the NdFeB blank by printing, the thickness of the NdFeB blank is 3.6 mm to 5.0 mm, and C=3.80 to 3.90.

[0027] According to the preparation method of the present invention, preferably, the terbium-containing material is attached to the NdFeB blank by printing, the thickness of the NdFeB blank is 5.1 mm to 6.5 mm, and C=5.30 to 5.40.

[0028] According to the preparation method of the present invention, preferably, the terbium-containing material is attached to the NdFeB blank by coating, the thickness of the NdFeB blank is 3.6 mm to 5.0 mm, and C=3.60 to 3.70.

[0029] According to the preparation method of the present invention, preferably, the heat treatment method is as follows: heat treatment at 600-960° C. for 1-15 h; and then heat treatment at 300-700° C. for 3-10 h.

[0030] The NdFeB magnet of the present invention is obtained by diffusing terbium into a NdFeB blank, and the coercive forces of the two conform to a certain relationship. This can be used to guide the production of NdFeB magnets with target coercive forces, improve production efficiency, and improve accuracy. The preparation method of the present invention has a simple process, can more accurately obtain the desired NdFeB magnet with a specific coercive force, and can be promoted and applied. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0032] The "coercive force" mentioned in the present invention, also called intrinsic coercive force, refers to the magnetic field intensity when the magnetic field is monotonically reduced to zero and then increased in the opposite direction from the saturated magnetization state of the magnet, so that the magnetization intensity decreases to zero along the saturation hysteresis loop, usually recorded as Hcj or MHc, and the unit is Oersted (Oe) or Ampere / meter (A / m). 1Oe = 79.6A / m.

[0033] The "vacuum degree" mentioned in the present invention refers to absolute vacuum degree; the smaller the value is, the higher the vacuum degree is.

[0034] <NdFeB magnets>

[0035] The NdFeB magnet of the present invention is obtained by diffusing terbium from a NdFeB blank with a coercive force A0, and the coercive force A1 of the NdFeB magnet and the coercive force A0 of the NdFeB blank conform to a certain relationship, which can be used to more accurately guide the production of NdFeB magnets with a certain coercive force.

[0036] In the present invention, the coercive force A1 of the NdFeB magnet and the coercive force A0 of the NdFeB blank satisfy the following relationship:

[0037] A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)-C;

[0038] The units of A1 and A0 are both kOe.

[0039] Among them, a is a constant, a is -25.00 to -20.00, b is a constant, b is 32.00 to 40.00, C is a constant, C is 3.20 to 5.80;

[0040] Wherein, ΔW is the weight gain percentage of terbium.

[0041] In the present invention, a is a constant, a is -25.00 to -20.00, preferably, a is -24.00 to -21.00, more preferably, a is -23.00 to -22.00. According to a specific embodiment of the present invention, a is a constant, a is -22.80 to -22.30.

[0042] In the present invention, b is a constant, b is 32.00-40.00, preferably, b is 35.00-38.00, more preferably, b is 36.00-37.00. According to a specific embodiment of the present invention, b is a constant, b is 36.10-36.90.

[0043] In the present invention, C is a constant, C is 3.20 to 5.80, preferably, C is 3.40 to 5.70, and more preferably, C is 3.50 to 5.50.

[0044] According to a specific embodiment of the present invention, C is a constant, and C is 3.60 to 5.36.

[0045] In the present invention, the weight gain percentage of terbium ΔW=(the weight of the NdFeB blank after terbium is attached-the initial weight of the NdFeB blank) / the initial weight of the NdFeB blank×100%.

[0046] In the present invention, the NdFeB blank is an R-Fe-B sintered magnet, with R2Fe 14 B is the main phase; wherein R is a rare earth element and must contain Nd. Specifically, the NdFeB blank contains Pr and Nd; based on the total weight of the NdFeB blank, the PrNd content is 28.3-31.5wt%, and the weight ratio of Pr to Nd is 1:3-1:4. The NdFeB blank contains dysprosium; based on the total weight of the NdFeB blank, the dysprosium content is greater than 0 and less than or equal to 2.5wt%.

[0047] In certain embodiments, the composition of the NdFeB blank is as follows: PrNd 28.3-31.5wt%, wherein the weight ratio of Pr to Nd is 1:3; B 0.89-0.96wt%, Dy 0.01-2.5wt%, Cu 0.01-0.1wt%, Co 0.01-1.0wt%, Nb 0-0.06wt%, Ga 0.01-0.25wt%, and Fe balance. Wherein, Pr is praseodymium, Nd is neodymium, B is boron, Dy is dysprosium, Cu is copper, Co is cobalt, Nb is niobium, Ga is gallium, and Fe is iron. Tb is terbium.

[0048] Based on the total weight of the NdFeB blank, the PrNd content is preferably 28.5-31wt%, more preferably 28.8-30wt%. The B content is preferably 0.91-0.96wt%, more preferably 0.93-0.95wt%. The Dy content is preferably 0.1-2.4wt%, more preferably 1.0-2.3wt%, more preferably 1.5-2.25wt%, for example, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.22wt%. The Cu content is preferably 0.03-0.1wt%, more preferably 0.06-0.08wt%, for example, 0.07wt%. The Co content is preferably 0.1-1.0wt%, more preferably 0.5-0.9wt%, for example, 0.55wt%, 0.6wt%, 0.65wt%, 0.71wt%, 0.75wt%, 0.80wt%. The Nb content is preferably 0.01-0.04wt%, more preferably 0.02-0.03wt%. The Ga content is preferably 0.07-0.25wt%, more preferably 0.15-0.23wt%, such as 0.18wt%, 0.21wt%.

[0049] In the present invention, the thickness of the NdFeB blank may be 2.5 mm to 8.0 mm, preferably 3.6 mm to 6.5 mm. In some embodiments, the thickness of the NdFeB blank is 3.6 mm to 5.0 mm. In other embodiments, the thickness of the NdFeB blank may be 5.1 mm to 6.5 mm.

[0050] The present invention finds that by controlling the weight gain percentage of attached terbium within a specific range, a neodymium iron boron magnet with a target coercive force can be obtained after diffusing terbium.

[0051] <Preparation method>

[0052] The present invention also provides a method for preparing a neodymium iron boron magnet, comprising the following steps:

[0053] (1) Providing a NdFeB blank; (2) Determining the weight gain percentage ΔW of terbium; (3) Testing steps; (4) Obtaining an attached magnet; (5) Heat treatment. This is conducive to obtaining a NdFeB magnet with a target coercive force. It is described in detail below.

[0054] Provide NdFeB blank

[0055] In the present invention, the NdFeB blank has a coercive force A0, wherein the unit of A0 is kOe. The NdFeB blank is an R-Fe-B sintered magnet, with R2Fe 14B is the main phase; wherein R is a rare earth element and must contain Nd. Specifically, the NdFeB blank contains Pr and Nd; based on the total weight of the NdFeB blank, the PrNd content is 28.3-31.5wt%, and the weight ratio of Pr to Nd is 1:3-1:4. The NdFeB blank contains dysprosium; based on the total weight of the NdFeB blank, the dysprosium content is greater than 0 and less than or equal to 2.5wt%.

[0056] In certain embodiments, the composition of the NdFeB blank is as follows: PrNd 28.3-31.5wt%, wherein the weight ratio of Pr to Nd is 1:3; B 0.89-0.96wt%, Dy 0.01-2.5wt%, Cu 0.01-0.1wt%, Co 0.01-1.0wt%, Nb 0-0.06wt%, Ga 0.01-0.25wt%, and Fe balance.

[0057] Based on the total weight of the NdFeB blank, the PrNd content is preferably 28.5-31wt%, more preferably 28.8-30wt%. The B content is preferably 0.91-0.96wt%, more preferably 0.93-0.95wt%. The Dy content is preferably 0.1-2.4wt%, more preferably 1.0-2.3wt%, more preferably 1.5-2.25wt%, for example, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.22wt%. The Cu content is preferably 0.03-0.1wt%, more preferably 0.06-0.08wt%, for example, 0.07wt%. The Co content is preferably 0.1-1.0wt%, more preferably 0.5-0.9wt%, for example, 0.55wt%, 0.6wt%, 0.65wt%, 0.71wt%, 0.75wt%, 0.80wt%. The Nb content is preferably 0.01-0.04wt%, more preferably 0.02-0.03wt%. The Ga content is preferably 0.07-0.25wt%, more preferably 0.15-0.23wt%, such as 0.18wt%, 0.21wt%.

[0058] In the present invention, the thickness of the NdFeB blank may be 2.5 mm to 8.0 mm, preferably 3.6 mm to 6.5 mm. In some embodiments, the thickness of the NdFeB blank is 3.6 mm to 5.0 mm. In other embodiments, the thickness of the NdFeB blank may be 5.1 mm to 6.5 mm.

[0059] Determine the weight gain percentage ΔW of terbium

[0060] According to the following formula, the weight gain percentage ΔW of terbium is determined, thereby determining the terbium adhesion amount;

[0061] A1-A0=a×(100×ΔW)2 +b×(100×ΔW)-C;

[0062] Wherein, A1 is the coercive force of the NdFeB magnet. A1 is known, that is, the coercive force of the target magnet (NdFeB magnet). The unit of A1 is kOe.

[0063] Wherein, a is a constant, a is -25.00 to -20.00, preferably, a is -24.00 to -21.00, more preferably, a is -23.00 to -22.00. b is a constant, b is 32.00 to 40.00, preferably, b is 35.00 to 38.00, more preferably, b is 36.00 to 37.00. C is a constant, C is 3.20 to 5.80, preferably, C is 3.40 to 5.70, more preferably, C is 3.50 to 5.50.

[0064] According to a specific embodiment of the present invention, the terbium-containing material is attached to the NdFeB blank by printing, the thickness of the NdFeB blank is 3.6 mm to 5.0 mm, and C=3.83.

[0065] According to another specific embodiment of the present invention, the terbium-containing material is attached to the NdFeB blank by printing, the thickness of the NdFeB blank is 5.1 mm to 6.5 mm, and C=5.33.

[0066] According to another specific embodiment of the present invention, the terbium-containing material is attached to the NdFeB blank by coating, the thickness of the NdFeB blank is 3.6 mm to 5.0 mm, and C=3.63.

[0067] In the present invention, ΔA=A1-A0 is the theoretical coercive force increase value. Thus, the weight gain percentage ΔW of terbium can be calculated based on the theoretical coercive force increase value and the known C constant. Thus, the terbium adhesion amount can be obtained based on the definition of the weight gain percentage ΔW of terbium. That is, the terbium adhesion amount is calculated based on the weight gain percentage ΔW of terbium and the initial weight of the NdFeB blank.

[0068] Inspection steps

[0069] After determining the amount of terbium deposited, a test step is performed. Test 100×ΔW. If it is between 0.45 and 0.80, the amount of terbium deposited is determined and step (4) is performed; otherwise, step (1) is performed again. Re-performing step (1) means that the coercive force of the NdFeB magnet needs to be reset.

[0070] Get the attachment magnet

[0071] According to the determined terbium attachment amount, the terbium-containing material is attached to two oppositely disposed surfaces of the NdFeB blank to obtain an attached magnet; wherein the two surfaces are perpendicular to the orientation direction of the NdFeB blank.

[0072] In the present invention, the terbium-containing material can be attached by printing or plating. The thickness direction is the orientation direction.

[0073] In the present invention, when the terbium-containing material is attached by printing, the terbium-containing material is terbium hydride. The steps of the printing method are as follows: terbium hydride is pulverized by mechanical processing, hydrogen crushing and air flow milling to obtain fine powder. The fine powder is mixed with an organic solvent to form a terbium hydride slurry of a certain concentration. The NdFeB blank is placed on a substrate rack, and the substrate rack is placed in a printing device. The terbium hydride slurry is poured on the printing screen. According to the amount of terbium attached, the terbium hydride slurry is coated on two opposite surfaces of the NdFeB blank perpendicular to the orientation direction, and then dried to obtain an attached magnet.

[0074] In the present invention, mechanical processing, hydrogen crushing and air flow milling can adopt those known in the art. The particle size of the fine powder is less than or equal to 15 μm, preferably less than or equal to 10 μm, and more preferably less than or equal to 6 μm. For example, it can be 7 μm, 6 μm, 5 μm, 4.5 μm, 4 μm, 3.5 μm, 3 μm.

[0075] In the terbium hydride slurry, the mass concentration of terbium hydride should be greater than or equal to 20wt%, preferably greater than or equal to 40wt%, more preferably greater than or equal to 70wt% and less than or equal to 90wt%. The organic solvent may be pine oil or an organic solvent similar to pine oil that can form terbium hydride into a relatively uniform slurry.

[0076] In the present invention, the terbium hydride slurry is coated on two opposite surfaces of the NdFeB blank and then dried. The drying temperature may be 110-200°C, preferably 120-180°C, and more preferably 120-160°C.

[0077] In the present invention, when attaching terbium-containing materials by coating, terbium palladium material can be used to attach terbium by magnetron sputtering. Specifically, it includes: placing the NdFeB blank on a substrate rack, preheating the substrate rack at 100-120°C, passing the substrate rack through the magnetron sputtering area at a uniform speed, and using terbium palladium as a target material during the period when the NdFeB blank passes through the magnetron sputtering area, so that terbium atoms form a terbium metal film on a surface of the NdFeB blank perpendicular to the orientation direction; after the substrate rack completely passes through the magnetron sputtering area, the substrate rack is cooled to below 100°C under the protection of an inert gas to obtain a first attached magnet; the first attached magnet is turned over, the first attached magnet is repeated with the above preheating steps, and then magnetron sputtering is performed on the other surface of the first attached magnet perpendicular to the orientation direction to form a terbium metal film, and then cooled to room temperature under the protection of an inert gas to obtain an attached magnet.

[0078] The two surfaces on which the terbium metal film is formed are opposite surfaces, both perpendicular to the orientation direction of the NdFeB blank. Before magnetron sputtering, the surface of the NdFeB blank can be cleaned to remove contaminants on the surface. This is conducive to more accurately obtaining NdFeB magnets with target coercive force.

[0079] Heat Treatment

[0080] The attached magnet is heat treated to obtain a neodymium iron boron magnet.

[0081] The heat treatment is performed under vacuum conditions. The vacuum degree is less than or equal to 0.5 Pa, preferably less than or equal to 0.3 Pa, more preferably less than or equal to 0.1 Pa, and even more preferably less than or equal to 0.01 Pa.

[0082] According to one embodiment of the present invention, the attached magnet is heat treated at 600-960°C for 1-15h (i.e., primary heat treatment); and then heat treated at 300-700°C for 3-10h (i.e., secondary heat treatment) to obtain a NdFeB magnet.

[0083] In the present invention, the temperature of the primary heat treatment is preferably 700 to 950°C, more preferably 850 to 930°C. The time of the primary heat treatment is preferably 5 to 13 hours, more preferably 10 to 12 hours. The temperature of the secondary heat treatment is preferably 400 to 600°C, more preferably 450 to 550°C. The time of the secondary heat treatment is preferably 4 to 9 hours, more preferably 5 to 7 hours.

[0084] <Test Method>

[0085] Determination of coercive force: The magnetic properties of NdFeB blanks and NdFeB magnets were measured at room temperature using a BA magnetometer (manufacturer: Germany Margery Magnetoelectric Co., Ltd., model: Permagraph C-200).

[0086] Example 1

[0087] (1) A NdFeB blank is provided, the composition of which is as follows: PrNd 28.84wt%, B 0.95wt%, Dy 2.22wt%, Cu 0.08wt%, Co 0.71wt%, Nb 0.03wt%, Ga 0.21wt%, Fe balance. The coercive force A0 is 19.65 kOe and the thickness is 4.0 mm.

[0088] (2) According to the following formula, the weight gain percentage ΔW of terbium is determined, thereby determining the amount of terbium adhesion;

[0089] A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)-C;

[0090] Wherein, A1 is the coercive force of the NdFeB magnet; A1 is 27.75kOe;

[0091] Among them, a is a constant, a is -22.62, b is a constant, b is 36.68, C is a constant, C is 3.83. Through calculation, 100×ΔW=0.45 is obtained.

[0092] (3) Check 100×ΔW, which is between 0.45 and 0.80, determine the amount of terbium deposition, and execute step (4).

[0093] (4) Terbium hydride fine powder and pine oil are mixed to prepare terbium hydride slurry with a concentration of 80wt%. The NdFeB blank is placed on a substrate rack, and the substrate rack is placed in a printing device. The terbium hydride slurry is poured on the printing screen. According to the determined terbium adhesion amount, the terbium hydride slurry is applied to two opposite surfaces of the NdFeB blank perpendicular to the orientation direction, and then dried at 120°C to obtain an adhered magnet.

[0094] (5) The attached magnet is subjected to a primary heat treatment at 925°C for 10 hours, cooled to below 90°C using argon gas, and then subjected to a secondary heat treatment at 500°C for 5 hours, cooled to below 60°C using argon gas, and the product is taken out to obtain a NdFeB magnet.

[0095] Examples 2 to 8 and Comparative Example 1

[0096] Except for the parameters shown in Table 1, other conditions of Examples 2 to 8 and Comparative Example 1 are the same as those of Example 1.

[0097] Table 1

[0098]

[0099] Note: ΔA=A1-A0; ΔA'=A1'-A0.

[0100] Example 9

[0101] (1) A NdFeB blank is provided, wherein the composition is as follows: PrNd 28.84wt%, B 0.95wt%, Dy 2.22wt%, Cu 0.08wt%, Co 0.71wt%, Nb 0.03wt%, Ga 0.21wt%, and Fe balance. The coercivity A0 is 19.65 kOe and the thickness is 6.0 mm.

[0102] (2) According to the following formula, the weight gain percentage ΔW of terbium is determined, thereby determining the amount of terbium adhesion;

[0103] A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)-C;

[0104] Wherein, A1 is the coercive force of the NdFeB magnet; A1 is 26.25kOe;

[0105] Among them, a is a constant, a is -22.62, b is a constant, b is 36.68, C is a constant, C is 5.33. Through calculation, 100×ΔW=0.45 is obtained.

[0106] (3) Check 100×ΔW, which is between 0.45 and 0.80, determine the amount of terbium deposition, and execute step (4).

[0107] (4) Terbium hydride fine powder and pine oil are mixed to prepare terbium hydride slurry with a concentration of 80wt%. The NdFeB blank is placed on a substrate rack, and the substrate rack is placed in a printing device. The terbium hydride slurry is poured on the printing screen. According to the determined terbium adhesion amount, the terbium hydride slurry is applied to two opposite surfaces of the NdFeB blank perpendicular to the orientation direction, and then dried at 120°C to obtain an adhered magnet.

[0108] (5) The attached magnet is subjected to a primary heat treatment at 925°C for 10 hours, cooled to below 90°C using argon gas, and then subjected to a secondary heat treatment at 500°C for 5 hours, cooled to below 60°C using argon gas, and the product is taken out to obtain a NdFeB magnet.

[0109] Embodiments 10 to 16

[0110] Except for the parameters shown in Table 2, other conditions of Examples 10 to 16 are the same as those of Example 9.

[0111] Table 2

[0112]

[0113] Note: ΔA=A1-A0; ΔA'=A1'-A0.

[0114] Embodiment 17

[0115] The difference from Example 1 is that A1 is different and the method of attaching terbium is different. This embodiment attaches terbium by magnetron sputtering coating. The specific steps are as follows:

[0116] (1) A NdFeB blank is provided, the composition of which is as follows: PrNd 28.84wt%, B 0.95wt%, Dy 2.22wt%, Cu 0.08wt%, Co 0.71wt%, Nb 0.03wt%, Ga 0.21wt%, Fe balance. The coercive force A0 is 19.65 kOe and the thickness is 4.0 mm.

[0117] (2) According to the following formula, the weight gain percentage ΔW of terbium is determined, thereby determining the amount of terbium adhesion;

[0118] A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)-C;

[0119] Wherein, A1 is the coercive force of the NdFeB magnet; A1 is 27.95kOe;

[0120] Among them, a is a constant, a is -22.62, b is a constant, b is 36.68, C is a constant, C is 3.63. Through calculation, 100×ΔW=0.45 is obtained.

[0121] (3) Check 100×ΔW, which is between 0.45 and 0.80, determine the amount of terbium deposition, and execute step (4).

[0122] (4) Place the NdFeB blank on a substrate rack and preheat the substrate rack at 100°C. Pass the substrate rack through the magnetron sputtering area at a uniform speed. While the NdFeB blank passes through the magnetron sputtering area, terbium palladium is used as a target material so that terbium atoms form a terbium metal film on a surface of the NdFeB blank perpendicular to the orientation direction. After the substrate rack completely passes through the magnetron sputtering area, cool the substrate rack to below 100°C under nitrogen protection to obtain a first attached magnet. Then turn the first attached magnet over, repeat the above preheating steps, perform magnetron sputtering on the other surface of the first attached magnet perpendicular to the orientation direction to form a terbium metal film, and then cool to room temperature under argon protection to obtain an attached magnet.

[0123] (5) The attached magnet is subjected to a primary heat treatment at 925°C for 10 hours, cooled to below 90°C using argon gas, and then subjected to a secondary heat treatment at 500°C for 5 hours, cooled to below 60°C using argon gas, and the product is taken out to obtain a NdFeB magnet.

[0124] The specific parameters and results are shown in Table 3.

[0125] Examples 18 to 24

[0126] Except for the parameters shown in Table 3, other conditions of Examples 18 to 24 are the same as those of Example 17.

[0127] Table 3

[0128]

[0129] Note: ΔA=A1-A0; ΔA'=A1'-A0.

[0130] It can be seen from the table that the difference between the coercive force A1 of the NdFeB magnet of the present invention and the coercive force A0 of the NdFeB blank basically satisfies the above relationship. The preparation method of the present invention can obtain a NdFeB magnet with a predetermined coercive force.

[0131] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A neodymium iron boron magnet, characterized in that: It is obtained by diffusing terbium from a neodymium iron boron blank having a coercive force A0. The coercive force A1 of the neodymium iron boron magnet and the coercive force A0 of the neodymium iron boron blank satisfy the following relationship: A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)-C; Wherein, a is a constant, a is -25.00~-20.00, b is a constant, b is 32.00~40.00, C is a constant, C is 3.20~5.80; ΔW is the weight gain percentage of terbium; the units of A1 and A0 are both kOe; The thickness of the NdFeB blank is 2.5 mm to 8.0 mm.

2. The NdFeB magnet according to claim 1, characterized in that: The NdFeB blank is an R-Fe-B sintered magnet. 14 B is the main phase; among them, R is a rare earth element and must contain Nd.

3. The NdFeB magnet according to claim 1, characterized in that: The NdFeB blank contains dysprosium; based on the total weight of the NdFeB blank, the dysprosium content is greater than 0 and less than or equal to 2.5wt%.

4. A method for preparing a neodymium iron boron magnet, characterized in that: The steps include: (1) providing a neodymium iron boron blank having a coercive force A0, wherein the unit of A0 is kOe; and the thickness of the neodymium iron boron blank is 2.5 mm to 8.0 mm; (2) According to the following formula, the weight gain percentage ΔW of terbium is determined, thereby determining the amount of terbium adhesion; A1-A0=a×(100×ΔW) 2 +b×(100×ΔW)-C; Wherein, A1 is the coercive force of NdFeB magnet; the unit of A1 is kOe; Among them, a is a constant, a is -25.00 to -20.00, b is a constant, b is 32.00 to 40.00, C is a constant, C is 3.20 to 5.80; (3) Check 100×ΔW. If it is between 0.45 and 0.80, determine the amount of terbium deposition and execute step (4); otherwise, execute step (1) again. (4) attaching the terbium-containing material to two oppositely disposed surfaces of the NdFeB blank according to the determined terbium attachment amount, thereby obtaining an attached magnet; wherein the two surfaces are perpendicular to the orientation direction of the NdFeB blank; (5) The attached magnet is heat treated to obtain a NdFeB magnet.

5. The preparation method according to claim 4, characterized in that: The NdFeB blank contains Pr and Nd. Based on the total weight of the NdFeB blank, the PrNd content is 28.3-31.5wt%, and the weight ratio of Pr to Nd is 1:3-1:

4.

6. The preparation method according to claim 4, characterized in that: C is 3.60~5.

50.

7. The preparation method according to claim 4, characterized in that: The terbium-containing material is attached to the NdFeB blank by printing, the thickness of the NdFeB blank is 3.6 mm to 5.0 mm, and C is 3.80 to 3.

90.

8. The preparation method according to claim 4, characterized in that The terbium-containing material is attached to the NdFeB blank by printing, the thickness of the NdFeB blank is 5.1 mm to 6.5 mm, and C is 5.30 to 5.

40.

9. The preparation method according to claim 4, characterized in that: The terbium-containing material is attached to the NdFeB blank by coating, the thickness of the NdFeB blank is 3.6 mm to 5.0 mm, and C is 3.60 to 3.

70.

10. The preparation method according to claim 4, characterized in that: The heat treatment method is as follows: heat treatment at 600-960°C for 1-15 hours; then heat treatment at 300-700°C for 3-10 hours.

Citation Information

Patent Citations

  • Rare-earth permanent magnet material and preparation method thereof

    CN105185498A

  • Method for preparing neodymium iron boron magnet through grain boundary diffusion

    CN107799294A

  • Method for increasing diffusion depth of neodymium iron boron grain boundary

    CN110120297A